Host Species Influence the Gut Microbiota of Endemic Cold-Water Fish in Upper Yangtze River - Xu, Liangliang; Xiang, Peng; Zhang, Baowen; Yang, Kun; Liu, Fenglin; Wang, Zesong; Jin, Yanjun; Deng, Longjun; Gan, Weixiong; Song, Zhaobin (Frontiers in Microbiology, 2022)
The fish gut microbiome plays an important role in nutrition absorption and energy metabolism. Studying the gut microbes of cold-water fish is important to understand the dietary adaptation strategies in extreme environments. Here, the gut samples of Schizothorax wangchiachii (SW, herbivorous), Schizothorax kozlovi (SK, omnivorous) and Percocypris pingi (PP, carnivorous) in the upper Yangtze River were collected and we sequenced 16S rRNA amplicon to study the potential relationship between gut microbes and host species. The results showed that gut microbial composition and diversity was significantly different between the three cold-water fishes. These fishes had different key taxa in their gut microbes, including bacteria involved in the breakdown of food (e.g., Cetobacterium, Aeromonas, and Clostridium sensu stricto 10). The highest alpha-diversity indices (e.g., Chao 1 index) were identified in the herbivore (SW), followed by the carnivore (PP), and the lowest in the omnivore (SK). Nonmetric multidimensional scaling (NMDS) results revealed that the gut microbial community of these species was different between host species. The neutral community model (NCM) model showed that the microbial community structure of SW was shaped by stochastic processes, and the highest species dispersal was found in SW, followed by PP, and the lowest in SK. The results of niche breadth agreed with these findings. Our results demonstrated that host species influenced the gut microbiome composition, diversity, and microbial community assembly processes of the three cold-water fishes. These findings implied that the variation of gut microbiome composition and function plays a key role in digesting and absorbing nutrients from different foods in cold-water fish.